The saboteur [large type] - Gross, Andrew, 1952- (Center Point Large Print, 2017)
"Based on a true story, in 1943 the Norwegian resistance is on a mission to thwart Nazi development of nuclear weapons. Parachuting onto the most unforgiving terrain in Europe, Kurt Nordstrum and his team attempt the most daring raid of the war"--